MANIFESTASI NEUROPSIKIATRIK PADA LUPUS ERITEMATOSUS SISTEMIK DI RSUD DR SOETOMO SURABAYA - Nadya Rinda Eka Rana,* Awalia,** Yetti Hernaningsih,*** Hanik Badriyah Hidayati**** (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION SYSTEMIC LUPUS ERYTHEMATOSUS SLE IS A CHRONIC AUTOIMMUNE INFLAMMATORY DISEASE WITH UNKNOWN CAUSES AND EXTENSIVE CLINICAL MANIFESTATIONS AND DIVERSE DISEASE PATHWAYS THE CLINICAL MANIFESTATIONS OF SLE ARE VERY DIVERSE INCLUDING THE INVOLVEMENT OF THE NERVOUS SYSTEM AND PSYCHIATRIC SYNDROME NEUROPSYCHIATRIC